2008
DOI: 10.1111/j.1470-6431.2008.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of time preference and credit card usage in compulsive buying behaviour

Abstract: College students represent a lucrative market for businesses selling a wide array of goods and services, including credit. One area of concern regarding credit debt is its association with compulsive buying behaviour. This study analysed compulsive buying behaviour within an economic framework using a college student sample. Data were collected from 7342 students enrolled in a major Midwestern university. Regression analysis revealed that income, rate of time preference, money attitudes, credit card usage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 15 publications
6
51
1
17
Order By: Relevance
“…The correlation test revealed that all three money attitude factors had positive relationship with compulsive buying (p < .01). The results support earlier research that suggest strong relationship between money attitude and compulsive tendencies (Roberts and Jones, 2001;Pirog and Roberts, 2007;Phau and Woo, 2008;Norum, 2008). Consumers high on compulsiveness would exhibit strong emotions about money.…”
Section: Findings and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The correlation test revealed that all three money attitude factors had positive relationship with compulsive buying (p < .01). The results support earlier research that suggest strong relationship between money attitude and compulsive tendencies (Roberts and Jones, 2001;Pirog and Roberts, 2007;Phau and Woo, 2008;Norum, 2008). Consumers high on compulsiveness would exhibit strong emotions about money.…”
Section: Findings and Discussionsupporting
confidence: 81%
“…The first model suggests that power accounts for 27.9% of compulsive buying. The results support earlier research (Hanley and Wilhelm, 1992;Roberts and Martinez, 1997;Roberts and Jones, 2001;Norum, 2008). Credit card factors of credit risk and payment, money attitude factors of status and anxiety and gender were removed from the model as they did not affect compulsiveness.…”
Section: Findings and Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A compulsive buyer has intend to experience more negative affect states than non-compulsive buyers (Miltenberger et al 2003). The many studies of compulsive buying show that higher levels of compulsive buying correlate with low self-esteem (Roberts 1998) or high anxiety (Norum 2008). The strongest motivating characteristics associated with compulsive buying appear to be materialistic tendencies (Dittmar 2005) and lack of impulse control (Desarbo and Edwards 1995;Billieux et al 2008).…”
Section: Compulsive Buying Tendency (Cbt)mentioning
confidence: 99%
“…Generación Y, también conocido como generación del Milenio -en inglés Millennial generation (los estudiantes nacidos después de 1980), es la generación más grande desde la generación del baby boom (Norum, 2008;Coomes, & DeBard, 2004 (Djamasbi, Siegel, & Tullis, 2010: 309). Estudiantes de la Generación Net han crecido en un mundo digital y esperan utilizar estas herramientas a su favor, en entornos de aprendizaje (Bajt, 2011: 54).…”
Section: Estudiantes Digitales Y No Nativos Digitalesunclassified